The Relationship of Contact Angle and Input Shaping Scheme in Automotive Wiper System - Salim, Mohd Azli; Noordin, Aminurrashid; Abd Munir, Fudhail; Mat Nuri, Nur Rashid (2012)
This study presents the modeling of two dimensional mathematical model of wiper system using Newtonian Law. Two dimensional mathematical models in x- and y-axis is found in differential equation form. The dynamics behavior of wiper system has a good response which instantaneously agreed which input or a disturbance happen during the operation of the system. Besides, in this study also investigated the effect of contact angle response in the flexible wiper assembly for forward and vice versa direction. The control scheme known as input shaping was applied to suppress the reversal noises and vibrations level in system. At the end of this study, the unwanted noise and vibration is reduced more than 25 percent compare with baseline result.